2010
DOI: 10.1089/pho.2009.2627
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Susceptibility to Coffee and Red Wine Staining at Different Intervals Elapsed from Bleaching: A Photoreflectance Spectrophotometry Analysis

Abstract: Bleached enamel was susceptible to red-wine staining at both 30 and 150 min after bleaching procedures, whereas coffee did not interfere with the bleaching process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 20 publications
4
51
0
6
Order By: Relevance
“…[30] found statistically significant differences between teeth treated with coffee and wine after bleaching, compared to a control group. However, another study[31] demonstrated that bleached enamel was susceptible to red wine staining after bleaching procedures, whereas coffee did not interfere with the bleaching process. In this study, although no statistically differences were observed between coffee and the control group at any time, there were statistically significant differences between red wine and the control group at all time points evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[30] found statistically significant differences between teeth treated with coffee and wine after bleaching, compared to a control group. However, another study[31] demonstrated that bleached enamel was susceptible to red wine staining after bleaching procedures, whereas coffee did not interfere with the bleaching process. In this study, although no statistically differences were observed between coffee and the control group at any time, there were statistically significant differences between red wine and the control group at all time points evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…18 Wine (Santome, Itupeva, Sã o Paulo, Brazil) and an alcoholic solution of tobacco (Nicotianatabacum L.) were used as chromogen agents. 21,22 To prepare the solution, a portion of 80 g of dry tobacco was mixed and chopped into slices of 7 mm (maximum) in 100 mL of alcohol 548Gay-Lussac. The solution was allowed to rest for 24 hours in a closed container.…”
Section: Methodsmentioning
confidence: 99%
“…For Liporoni et al (2010), enamel bleached with 35% hydrogen peroxide was susceptible to the pigmentation of wine, but coffee does not interfere with the whitening process. The authors report the possibility that hydrogen peroxide is a facilitator for this pigmentation, due to the increased porosity of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the results of different studies can be justified by the exposure time to bleaching agents, which leads to a tendency to variable effects of pigmented agents (LIPORONI et al, 2010). Furthermore, the action of carbamide peroxide and color stability differs significantly from hydrogen (LIMA et al, 2009).…”
Section: Discussionmentioning
confidence: 99%